The Enhancement of Educational Quality Through Personnel Management: A Case Study of MAN 2 in the Bandung Regency - Kholiqoh (Zona Education Indonesia, 2023)
The main problems in this study are planning, organizing, planning human resources, supervising in improving the quality of education in MAN 2 Bandung Regency. Methodologically, this research is qualitative research by searching, analyzing, and intervating the data found through interviews, observations (observations) and study documents. The data that has been collected is checked for validity through data validity standards, in the form of trustworthiness and certainty. The data analysis techniques carried out are reducing data, presenting data and drawing conclusions from research results. This study aims to find and examine more deeply the effectiveness of human resource management in MAN 2 Bandung Regency. Data are obtained through observation, where researchers function as instruments to make observations, in-depth interviews with primary data sources and study documentation. Data is analyzed by interactive analysis through 3 activities, namely data reduction, data presentation, and drawing conclusions. From the results of this study, it can be explained that the Human Resource Management of Educators in MAN 2 Bandung District includes: 1) HR planning is designed and compiled systematically and based on school independence by taking into account the characteristics of the school. 2) HR recruitment is carried out by prioritizing the principle of professionalism. 3) The selection in the value has met the professional element. 4) The training conducted has had a positive impact and influence both for the school and personally. 5) Work assessment is carried out using two aspects, namely quantitative and qualitative aspects. 6) Compensation. 7) Termination of employment. Meanwhile, improving the quality of human resources of educators in MAN 2 Bandung District that the efforts of school principals in improving the quality of education are seen in input, process, and output indicators. The principal's efforts in improving the quality of education in relation to input indicators are preparing professional educators; both through coaching; discussions and meetings; academic seminars; include training, workshops; and training, refining student recruitment strategies through promotion